2015
DOI: 10.2147/ott.s78567
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis and treatment of acute lymphoblastic leukemia relapse after allogeneic hematopoietic stem cell transplantation

Abstract: Relapse of acute lymphoblastic leukemia remains a major cause of death in patients following allogeneic hematopoietic stem cell transplantation. Several factors may affect the concurrence and outcome of relapse, which include graft-versus-host disease, minimal residual disease or intrinsic factors of the disease, and transplantation characteristics. The mainstay of relapse prevention and treatment is donor leukocyte infusions, targeted therapies, second transplantation, and other novel therapies. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Relapse-related death rates were higher among ALL patients. In general, the main cause of mortality was relapsing among ALL patients after allogeneic stem cell transplantations [18]. In our cohort, frequency of relapse rates in post-transplant ALL patients might be due to the general opinion of weak graft-versus-malignancy effect, but also [19] it might be due to early relapsing of patients before development of graft-versus-leukemia effect.…”
Section: Discussionmentioning
confidence: 59%
“…Relapse-related death rates were higher among ALL patients. In general, the main cause of mortality was relapsing among ALL patients after allogeneic stem cell transplantations [18]. In our cohort, frequency of relapse rates in post-transplant ALL patients might be due to the general opinion of weak graft-versus-malignancy effect, but also [19] it might be due to early relapsing of patients before development of graft-versus-leukemia effect.…”
Section: Discussionmentioning
confidence: 59%
“…However, Solomon et al (2016) reported that the relapse rate was not different between ALL and AML after allo-HSCT. It has been reported by other studies that ALL could benefit from the GVL effect by DLI intervention (Yan et al, 2012;Chen et al, 2015), including patients with ALL relapse post-transplantation (Terwey et al, 2013;Yan et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…We also analysed GRFS, and found that the 1year and 3-year GRFS of HID transplants was equivalent to those of the MSD and MUD transplants. It has been reported by other studies that ALL could benefit from the GVL effect by DLI intervention (Yan et al, 2012;Chen et al, 2015), including patients with ALL relapse post-transplantation (Terwey et al, 2013;Yan et al, 2016). Increasingly, improvements have been made in prophylaxis for GVHD, such as the use of T-cell depletion in vivo by means of Cy or ATG (Bashey et al, 2013;Luo et al, 2014;Chang et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…However, allogeneic HSCT offers the best and may be the only chance for cure in adult patients with relapsed ALL [103][104][105]. GVHD, MRD, intrinsic factors of the disease and transplantation characteristics affect the occurrence as well as the outcome of ALL relapse after HSCT [106]. Unfortunately, the prognosis of patients with ALL who relapse after HSCT and those who are refractory to chemotherapy is extremely poor with ˂ 10% long-term survival [23,78,107].…”
Section: Relapse Of All Before and After Hsctmentioning
confidence: 99%
“…Management of ALL relapse post-HSCT includes: tapering of immunosuppressive therapy; salvage chemotherapy followed by second allogeneic HSCT; pre-emptive immunotherapy in the form of DLI with frequent MRD monitoring; post-transplantation maintenance therapy; the use of novel and targeted therapies in post-HSCT to prevent further relapses; and enrollment in clinical trials [106][107][108].…”
Section: Relapse Of All Before and After Hsctmentioning
confidence: 99%